Monitoreo de ácidos grasos trans en Córdoba, Argentina 2014 - Barrientos, Viviana; Maldonado, Fabiana; Massari, Mariano; Ferrayoli, Carlos (2024)
Fil: Barrientos, Viviana. Centro de Excelencia en Procesos Córdoba; Argentina.